Fiona solved the equation shown 1/2-1/3(6x-3)=-13/2 what is the missing step of her solution?
![Fiona solved the equation shown 12136x3132 what is the missing step of her solution class=](https://us-static.z-dn.net/files/ddc/1eddd2b7213bbcaf29eb0ff52e7da5d7.jpg)
Answer:
Summation of the non variable Expression within the quality sign
1/2 + 1-2x= -13/2
3/2-2x= -13/2
Step-by-step explanation:
1/2-1/3(6x-3)=-13/2
First step
Using the distributive property to simply
1/2-(6x/3)+(3/3)=-13/2
1/2 -2x +1 = -13/2
Second step
Summation of the non variable Expression within the quality sign
1/2 + 1-2x= -13/2
3/2-2x= -13/2
Third step
Isolating the variable Expression by using the addition property of equality
-2x = -13/2 - 3/2
-2x = -16/2
Fourth step
Isolating the variable by using the division property of equality
-2x = -16/2
X = -16/2 * -1/2
X = -16/-4
X= 4
Answer:
Simplify by combining like terms
Step-by-step explanation: